Renal replacement therapy in critically ill patients receiving extracorporeal membrane oxygenation - Askenazi, David J; Selewski, David T; Paden, Matthew L; Cooper, David S; Bridges, Brian C; Zappitelli, Michael; Fleming, Geoffrey M (Clinical journal of the American Society of Nephrology, 2012)
Extracorporeal membrane oxygenation (ECMO) is a lifesaving procedure used in neonates, children, and adults with severe, reversible, cardiopulmonary failure. On the basis of single-center studies, the incidence of AKI occurs in 70%-85% of ECMO patients. Those with AKI and those who require renal replacement therapy (RRT) are at high risk for mortality, independent of potentially confounding variables. Fluid overload is common in ECMO patients, and is one of the main indications for RRT. RRT to maintain fluid balance and metabolic control is common in some but not all centers. RRT on ECMO can be performed via an in-line hemofilter or by incorporating a standard continuous renal replacement machine into the ECMO circuit. Both of these methods require specific technical considerations to provide safe and effective RRT. This review summarizes available epidemiologic data and how they apply to our understanding of AKI pathophysiology during ECMO, identifies indications for RRT while on ECMO, reviews technical elements for RRT application in the setting of ECMO, and finally identifies specific research-focused questions that need to be addressed to improve outcomes in this at-risk population.